Electrospun Pd-doped mesoporous carbon nano fibres as catalysts for rechargeable Li–O2 batteries. Issue 62 (14th June 2016) - Martinez Crespiera, S.; Amantia, D.; Knipping, E.; Aucher, C.; Aubouy, L.; Amici, J.; Zeng, J.; Francia, C.; Bodoardo, S.
Abstract : Mesoporous carbon nanofibres doped with palladium nanoparticles (Pd CNFs) are synthesized by electrospinning with subsequent thermal treatment processes and used as electro-catalysts at the oxygen cathode of Li–O2 batteries. Abstract : Mesoporous carbon nanofibres doped with palladium nanoparticles (Pd CNFs) are synthesized by electrospinning with subsequent thermal treatment processes and used as electro-catalysts at the oxygen cathode of Li–O2 batteries. FESEM images show that the spherical Pd nanoparticles (NPs) are homogeneously dispersed on the surface of CNFs and X-ray diffraction (XRD) measurements display a fcc structure of Pd. The surface area of the nanocomposite CNFs is greatly increased with the incorporation of the metal NPs up to 600 m 2 g −1 and the presence of the metal promotes graphitization of the carbon. Addition of the N -[(aminoethyl)aminopropyl]trimethoxysilane additive in the precursor solution for electrospinning allows the reduction of the Pd NPs particles size, preserving the highly mesoporous N-doped large surface area and graphitic-nitrogen groups of the carbon nanofibres. Incorporating with a Pd/CNFs catalysed cathode, the Li–O2 battery shows a very low voltage gap of 0.48 V vs. Li + /Li between the terminal discharge and charge voltages, as the recharge occurs at a potential underneath 4.0 V vs. Li + /Li for about 90 cycles at the curtailed capacity of 200 mA h g −1 . The low recharge voltage can relieve parasitic reactions due to the decomposition of electrolyte and favour a longer cycle life.